PENDUGAAN KANDUNGAN BIJIH BESI DENGAN METODE GEOLISTRIK RESISTIVITY 2D, IP, DAN GEOMAGNET DI PT. ARIES IRON MINING DESA TUMBANG TILAP, KALIMANTAN TENGAH - Valentinus Singgih Yudanto; Excelsior T P; Luthfi Wahyudi (KURVATEK, 2018)
The study was conducted at PT. Aries Iron Mining Tumbang Tilap, District Mentaya Hulu, Kotawaringin Timur, East Kalimantan province.Exploration of the geomagnetic method parameter used to study susceptibility of these methods and geoelectric parameters used to study iron ore with this method is conductive and resistive properties. Geomagnetic data is processed using surfer program, the results of the program are used to determine the retrieval surfer geoelectric. Geoelectric method can provide a snapshot below the soil surface is generally without excavation geophysical methods using methods Geoscan (2D Resistivity and Induced Polarization). IP geoelectric investigation using dipole-dipole configuration, and is limited to the determination of the variation of the subsurface resistivity and chargeability vertically or horizontally